A tutela jurisdicional coletiva pós reforma trabalhista: ação coletiva e acesso à justiça - Gouveia, Bruno Paiva (2022)
An evolution of procedural law was necessary to adapt to the new needs of the contemporary world, in order to ensure the effective protection of interests that go beyond the limits of inter-individual relations. In the Brazilian scenario, showing concern with the growing mass conflicts, the importance of collective tutelage was verified and a collective procedural microsystem was created, which is a reference among civil law countries. Despite this, in recent years, procedural legislation has opted for the increase of multi-individual guardianship techniques, through decisions rendered in so-called sampling judgments, to the detriment of collective guardianship. In the labor area, the Federal Constitution of 1988, in its article 8, item III, attributed to unions the defense of collective or individual rights and interests of the category, including in legal matters. Even after the advent of the Constitution, the Labor Courts maintained its restrictive posture in relation to the replacement of labor procedures, with the edition of Precedent n. 310 by the Superior Labor Court. Due to the position of the Federal Supreme Court, which recognized the constitutionality of broad procedural replacement by union entities, in 2003, Precedent n. 310 was cancelled by the TST. Even after the cancellation of Precedent n. 310, decisions by the Labor Court restricting the scope of collective actions for the defense of injured workers are frequent. The labor reform (Law 13,467/17) brought changes in procedural rules, creating obstacles to individual worker access to the Labor Court. Recent legislative changes do not affect collective actions, which play a fundamental role in enabling workers' access to justice, without compromising their employment and without the fear of facing obstacles to a new placement in the labor market. Collective actions reduce the financial imbalance existing between the parties in individual proceedings, allow the Judiciary to assess injuries that individually would not have great economic repercussions, and reduce the processes in progress before the Judiciary Branch. The work of union entities and the Public Prosecutor's Office is essential for collective actions to achieve their objective of promoting real access of workers to justice and the implementation of social rights guaranteed in the Constitution and in the labor legislation